ELECTRICITY GENERATION FROM BIOGAS - MARTINEZ, DAIANA G.; KITAMURA, DANILO S.; SILVA, FELIPE P.; SOUZA, SAMUEL N.M.; BASTOS, RAFAELA K.; SOUZA, CASSIA R.B. (Revista Brasileira de Engenharia de Biossistemas, 2013)
This study aimed to evaluate the system of electricity generation through the use of biogas from a swine production unit, located in the municipality of São Miguel do Iguaçu, taking into account aspects related to consumption of biogas generation electricity. A flow meter aiming at recording the flow of biogas was used, it was used GCP-22 is the control equipment and generator protection; data acquisition is also performed using energy analyzers. These analyzers record production / consumption in a time interval of 15 minutes. It was observed that the month of May had the highest consumption, reaching approximately 18 m³ of biogas. Evaluating the period, the total energy generated from bike generator set obtained an approximate value 110.3 MWh. The power consumption of the property was 55 MWh, and 16.8 MWh consumed in the distribution network. The surplus energy exported to the distribution network was approximately 72 MWh. The average generation for the period was 605.93 kWh. The average consumption of biogas generator set by bike was 49.3 Nm³.h.